If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 4) = 9x + -6 Reorder the terms: 5(4 + x) = 9x + -6 (4 * 5 + x * 5) = 9x + -6 (20 + 5x) = 9x + -6 Reorder the terms: 20 + 5x = -6 + 9x Solving 20 + 5x = -6 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 20 + 5x + -9x = -6 + 9x + -9x Combine like terms: 5x + -9x = -4x 20 + -4x = -6 + 9x + -9x Combine like terms: 9x + -9x = 0 20 + -4x = -6 + 0 20 + -4x = -6 Add '-20' to each side of the equation. 20 + -20 + -4x = -6 + -20 Combine like terms: 20 + -20 = 0 0 + -4x = -6 + -20 -4x = -6 + -20 Combine like terms: -6 + -20 = -26 -4x = -26 Divide each side by '-4'. x = 6.5 Simplifying x = 6.5
| (8e).1= | | 4.7+1.2x=2.2x | | 6n-202=4(2-6n) | | 24+3n=1.5 | | 9x^3+3x^2-30x=0 | | 11.7b+5=5.2b+33.60 | | 14+b=2-3b | | F(3)=2x+10 | | 2(3-5a)-4a=9a-224 | | 4.2x+68=6.7x+13 | | 1/3x-7=-11 | | (0+c)+12= | | 4(3+5x)-5=27 | | 4x-3=4x-3x-6 | | 4g-5+2g=19 | | R=(2.18)3.4 | | 4x-5+x-5=50 | | log(2)(6X+7)=6 | | 7u+2=5u | | (M-1)(2m-5)=0 | | (6r-7s+8t)-(2r-3s+4t)= | | -7.70=10.8-7.4t | | 24+3n=24+1.5 | | 2x^3-7x^2-8x+28=0factoring | | 5d^2+9d-18=0 | | 7.9a+3.25=-14.13 | | 6x-1+7x=90 | | 7.9a+3.25=-14.1 | | 2x-9y=8 | | 4y=-6x-2 | | X^2-4ix-13=0 | | 6(d+6)-8=2*d+30 |